Formulación de un plan de negocios para la creación de una empresa de ciclopaseos en la ciudad de Santa Marta (2022)
The territory of Magdalena has different qualities to be powerful in the tourist sector at national level, this is due to the amount of flora and fauna and its natural riches that this Department has, this project was born by a particular taste for tourism as a form of social interaction and knowledge and valuation of the strengths that exist in this branch, in that context, the ecological potential is identified, and capitalizing it by means of the cycle walk in the city of Santa Marta and its surroundings, highlighting that this territory is privileged by all the components with which it counts, such as the seas, rivers, mountains and their beautiful ecosystems that can be enjoyed. By the above written, it is necessary to implement this business plan of the cycle tours in the tourist sectors of this city, since frequently these sites are visited by tourists from all parts of the country and abroad, our service of the cycle tour, it is aimed at any type of person of greater age, after fulfilling the requirements demanded by the company will benefit from the services, emphasizing the importance of making this practice for the human body contributing to maintain good health, apart from that customers can enjoy the wonders offered by the natural landscapes, which are located in the Sierra Nevada de Santa Marta In turn, the tours that are provided to the clients are: Minca tours, shell bay tours and mango pass tours, will also be arranged a headquarters in the Minca district, because that place is one of the most visited by tourists, the main idea is to meet the different needs of customers who are willing to use our service and fulfill their expectations, this practice is being handled in other countries of the world and it is time to plan and put it into practice in this part of the country, highlighting that it has all the qualities to carry out this business plan, for the present investigation, a study is carried out that will be analyzed from a qualitative and quantitative perspective, carrying out studies of an exploratory scope in order to know more details of the subject which has not been studied and which is not known. find data at the municipal level, a variable is defined together with some indicators and several observations are made of the current situation of tourism in the city and its surroundings that can know the tourist potential of the city of Santa Marta and the number of people interested in doing ecological tourism and the amount of resources that tourists would be willing to invest in tourism and cycle tours, this information will be obtained by collecting information from different sources such as primary and secondary